Pengaruh Dewan Komisaris Independen, Komite Audit, Ukuran Perusahaan Dan Profitabilitas Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2016-2020 - Nur Hanifah; Damayanti Damayanti; M. Iqbal Harori (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
ABSTRACT : The purpose of this study was to determine the effect of the independent variables, namely the independent board of commissioners, audit committee, firm size and profitability on the dependent variable, namely corporate tax avoidance. Sampling used purposive sampling method, and obtained 10 sample companies from a population of 26 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The analytical method used is panel data regression analysis which is processed using the e-views 9 program. The results of this study indicate that partially independent board of commissioners/variables, company size and profitability have a significant effect on the avoidance of tax. While the audit committee has no significant effect on tax avoidance. The results showed that simultaneously independent board of commissioners, audit committee, firm size and profitability had a significant effect on tax avoidance. Keywords: Independent Board of Commissioners, Audit Committee, Company Size, Profitability and Tax Avoidance